2015
DOI: 10.1016/j.vetmic.2014.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the cellular proteome of the nucleocapsid protein from a highly pathogenic isolate of porcine reproductive and respiratory syndrome virus identifies PARP-1 as a cellular target whose interaction is critical for virus biology

Abstract: HighlightsProteomics was used to identify the cellular interactome of PRRSV N protein.The interactome included translation factors and PARP-1.Inhibition of PARP-1 by the small molecule 3-AB resulted in a decrease in virus infection.Sustained treatment of PRRSV infected cells with 3-AB suggested resistance free antiviral activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…The nucleocapsid protein of porcine reproductive and respiratory syndrome virus (PRRSV) binds to PARP1, and the interaction is critical for viral replication, since the use of a PARP inhibitor led to inhibited viral growth (156). In an intriguing parallel, Grunewald et al have shown that the nucleocapsid proteins of both ␣and ␤-coronaviruses are MARylated during infection (157).…”
Section: Parps In Proviral Responsesmentioning
confidence: 99%
“…The nucleocapsid protein of porcine reproductive and respiratory syndrome virus (PRRSV) binds to PARP1, and the interaction is critical for viral replication, since the use of a PARP inhibitor led to inhibited viral growth (156). In an intriguing parallel, Grunewald et al have shown that the nucleocapsid proteins of both ␣and ␤-coronaviruses are MARylated during infection (157).…”
Section: Parps In Proviral Responsesmentioning
confidence: 99%
“…Although several studies have been focused on the relationship between PRRSV viral proteins such as N [17,34], NSP1 [35,36], NSP2 [37] and whole virion [38,39] and the host cellular proteins, cellular interactome of PRRSV NSP12 has not been reported to the best of our knowledge. Here, high throughput proteomics coupled with immunoprecipitated strategy was used to identify and quantify cellular proteins which potentially interacted with PRRSV NSP12 and participated in viral replication,…”
Section: Discussionmentioning
confidence: 99%
“…The interactome of PRRSV NSP12 was determined by high-affinity GFP pull-down coupled with label free mass spectrometry-based approach, which we have used previously to study virus/host protein interactions [16][17][18][19]. Our data identified112 cellular proteins probably interacted with NSP12, and these proteins were mainly nucleic acid binding proteins or chaperones and were grouped into several distinct functional clusters.…”
Section: Ifn-mediated Antiviral Responses In Order To Gain Time For Vmentioning
confidence: 94%
See 2 more Smart Citations